Avaliação da qualidade interna e da composição lipídica dos ovos de galinhas poedeiras em sistema cage-free alimentadas com sementes de maracujá - Ramos, Juliano Carneiro (Brasil, 2024)
Passion fruit seeds represent a promising alternative ingredient in animal feed, offering nutritional and economic benefits. Its composition rich in fibers, proteins, minerals, and bioactive compounds makes it a viable dietary supplement for various species. Thus, an experiment was conducted at Gleba da Vila Amazônia, in the municipality of Parintins/AM, aiming to evaluate the internal quality and lipid composition of eggs from cage-free laying hens fed with diets containing passion fruit seeds. A total of 144 commercial laying hens from the Embrapa 051 lineage, aged 47 weeks, were used, distributed in 24 compartments of a conventional poultry house. The experiment was conducted in a completely randomized design, with four treatments, each with six replications, and each replication consisting of 6 eggs. The treatments consisted of four experimental diets with increasing levels of inclusion of passion fruit seeds (0%, 3%, 6%, and 9%). In the evaluation of egg quality, the treatments with seed inclusions did not influence the weight of the eggs, yolk weight, yolk index, shell thickness, and yolk color. However, there was a quadratic effect for the albumen height and the Haugh unit. The best estimate for the albumen height was 8.80mm, with an inclusion of 5.40% of the seeds. Meanwhile, the best estimate for the Haugh unit was 94.09, with an inclusion of 5.28% of the seeds. Furthermore, the inclusions of the seeds demonstrated a linear influence on the total lipid composition of the eggs. The result showed that the inclusion of 9% of passion fruit seeds can be indicated to increase the lipid content of the eggs.